(untitled) (Architecture Image Studies, 2026)
Mathematical problem-solving ability is an essential competency in mathematics learning, yet many students still experience difficulties in developing effective problem-solving strategies. This study aims to examine the effectiveness of the CORE (Connecting, Organizing, Reflecting, and Extending) learning model assisted by electronic student worksheets (E-LKPD) in enhancing students’ mathematical problem-solving ability, as well as to describe students’ problem-solving characteristics based on visual, auditory, and kinesthetic learning styles. Employing a mixed-methods approach with a sequential explanatory design, quantitative data were obtained through a pretest–posttest control group design, while qualitative data were collected through tests, questionnaires, and interviews. The results indicate that the implementation of the CORE learning model supported by E-LKPD contributes positively to students’ engagement in understanding problems, organizing solution strategies, and reflecting on mathematical thinking processes. Furthermore, variations in problem-solving characteristics were observed among students with different learning styles, suggesting that learning preferences influence how students construct and apply problem-solving strategies. These findings highlight the importance of integrating constructivist learning models with interactive digital media and adaptive instructional design to support the development of students’ mathematical problem-solving ability. Future research is encouraged to explore learning designs that more optimally accommodate diverse student learning characteristics.